Endocuff-assisted vs. standard colonoscopy in the fecal occult blood test-based UK Bowel Cancer Screening Programme (E-cap study): a randomized trial - Bhattacharyya, Rupam; Chedgy, Fergus; Kandiah, Kesavan; Fogg, Carole; Higgins, Bernard; Haysom-Newport, Ben; Gadeke, Lisa; Thursby-Pelham, Fergus; Ellis, Richard; Goggin, Patrick; Longcroft-Wheaton, Gaius; Bhandari, Pradeep (Endoscopy, 2017)
Background and study aims Up to 25 % colorectal adenomas are missed during colonoscopy. The aim of this study was to investigate whether the endocuff could improve polyp detection in an organized bowel cancer screening program (BCSP).Patients and methods This parallel group, single-blinded, randomized controlled trial included patients with positive fecal occult blood test (FOBT) who were attending for BCSP colonoscopy. The primary outcome was the number of polyps per patient. Secondary outcomes included the number of adenomas per patient, adenoma and polyp detection rates, and withdrawal times.Results A total of 534 BCSP patients were randomized to endocuff-assisted or standard colonoscopy. The mean age was 67 years and the male to female ratio was 1.8:1. We detected no significant difference in the number of polyps per patient (standard 1.8, endocuff 1.6; P = 0.44), adenomas per patient (standard 1.4, endocuff 1.3; P = 0.54), polyp detection rate (standard 69.8 %, endocuff 70.3 %; P = 0.93), adenoma detection rate (standard 63.0 %, endocuff 60.9 %; P = 0.85), advanced adenoma detection rate (standard 18.5 %, endocuff 16.9 %; P = 0.81), and cancer detection rate (standard 5.7 %, endocuff 5.3 %; P = 0.85). The mean withdrawal time was significantly shorter among patients in the endocuff group compared with the standard colonoscopy group (16.9 vs. 19.5 minutes; P < 0.005). The endocuff had to be removed in 17/266 patients (6.4 %) because of inability to pass through the sigmoid colon.Conclusions This study did not find improved polyp or adenoma detection with endocuff-assisted colonoscopy in the FOBT-positive BCSP population. A shorter withdrawal time with endocuff may reflect improved views and stability provided by the endocuff.Trial registered at ClinicalTrials.gov (NCT02529007).